Hepatocellular carcinoma recurrence in patients with curative resection or ablation: impact of HCV eradication does not depend on the use of interferon. Issue 1 (28th October 2016) - Petta, S.; Cabibbo, G.; Barbara, M.; Attardo, S.; Bucci, L.; Farinati, F.; Giannini, E. G.; Tovoli, F.; Ciccarese, F.; Rapaccini, G. L.; Di Marco, M.; Caturelli, E.; et al.
Summary: Background: In HCV‐infected cirrhotic patients with successfully treated early hepatocellular carcinoma (HCC), the time to HCC recurrence and the effects of sustained viral eradication (SVR) by interferon (IFN)‐based or IFN‐free regimens on HCC recurrence remain unclear. Aim: To perform an indirect comparison of time to recurrence (TTR) in patients with successfully treated early HCC and active HCV infection with those of patients with SVR by IFN‐based and by IFN‐free regimens. Methods: We evaluated 443 patients with HCV‐related cirrhosis and Barcelona Clinic Liver Cancer Stage A/0 HCC who had a complete radiological response after curative resection or ablation. Active HCV infection was present in 328, selected from the Italian Liver Cancer group cohort; 58 patients had SVR achieved by IFN‐free regimens after HCC cure, and 57 patients had SVR achieved by IFN‐based regimens after HCC cure. Individual data of patients in the last two groups were extracted from available publications. Results: TTR by Kaplan–Meier curve was significantly lower in patients with active HCV infection compared with those with SVR both by IFN‐free ( P = 0.02) and by IFN‐based ( P < 0.001) treatments. TTR was similar in patients with SVR by IFN‐free or by IFN‐based ( P = 0.49) strategies. Conclusion: In HCV‐infected, successfully treated patients with early HCC, SVR obtained by IFN‐based or IFN‐free regimens significantly reduce tumour recurrence without differences related to the anti‐viral strategy used.